Evaluation of Waste Management System in İzmir-Karaburun Peninsula From Sustainability Perspective - Hajatnia, Haniyeh; Ökten, Hatice Eser (Izmir Institute of Technology, 2022)
Global solid waste generation is constantly rising, hence the need for management strategies that implement environmental improvements. The sustainable municipal solid waste management strategy for municipalities must include collection and transportation. The collection and transportation sector have been neglected while it is one of the most significant polluters. As a result, this study aims to model municipal solid waste transportation using Life Cycle Assessment (LCA) software which we used CCalC2 for this study and CML2001 methodology was used. To demonstrate how different approaches to waste management through transportation can reduce environmental impacts, LCA modeling was done for the three districts of Urla, Çeşme, and Karaburun, all of which are located on the Karaburun Peninsula. Each district was assigned three scenarios, with Scenario 0 representing current municipal practices, Scenario 1 representing a 50% reduction in plastic waste, and Scenario 2 representing a 50% reduction in all renewables. Results showed that only plastic separation might not be enough to achieve significant e reductions in environmental impacts. It has been demonstrated that in the transportation sector of Urla and Çeşme, Scenario 1 had a CO2 reduction of 3.7% and Karaburun had a CO2 reduction of 3.8% while Scenario 2 represented at least a 20% reduction of carbon footprint in all three districts. Findings of this research will support municipalities in the roadmaps they will choose for the Municipal Solid Waste Management applications.

Küresel katı atık üretimi ile birlikte çevresel indikatörlerde iyileşmeye yol açabilecek yönetim stratejilerine ihtiyaç artmaktadır. Belediyeler için sürdürülebilir belediye katı atık yönetimi stratejisi, toplama ve taşımayı içermelidir. Toplama ve taşıma sektörü en önemli kirleticilerden biri olmakla birlikte ihmal edilmiştir. Sonuç olarak bu çalışma, belediye katı atık taşımacılığını Yaşam Döngü Değerlendirmesi (YDD) yazılımı kullanarak modellemeyi amaçlamaktadır. Ulaşım yoluyla atık yönetimine farklı yaklaşımların çevresel etkileri nasıl azaltabileceğini göstermek için, tümü Karaburun Yarımadasında bulunan Urla, Çeşme ve Karaburun ilçeleri için YDD modellemesi yapıldı. Her bölgede, halihazırdaki belediye uygulamalarını temsil eden Senaryo 0, plastik atıklarda %50'lik bir azalmayı temsil eden Senaryo 1 ve tüm yenilenebilir kaynaklarda %50'lik bir azalmayı temsil eden Senaryo 2 olmak üzere üç senaryo tanımlanmıştır. Sonuçlar, çevresel etkiyi azaltma hedefine ulaşmak için yalnızca plastikleri ayırmanın yeterli olmayabileceğini göstermektedir. Urla ve Çeşme ulaşım sektöründe senaryolardan birinde % 3,7 CO2 azaltımının olduğu ve Karaburun'da % 3,8 CO2 azaltımının olduğu, Senaryo 2'nin ise her üç ilçede de karbon ayak izinde en az % 20'lik bir azalmayı temsil ettiği ortaya konmuştur. Bu araştırmadan elde edilen bulgular, ilgili belediyelerin sürdürülebilir Evsel Katı Atık Yönetimi uygulamalarında izleyecekleri yol haritasını belirlemelerinde destek olacaktır.
İzmir-karaburun Yarımadasındaki Atık Yönetim Sisteminin Sürdürebilirlik Perspektifinden Değerlendirilmesi
Thesis (Master)--Izmir Institute of Technology, Environmental Engineering, Izmir, 2022
Includes bibliographical references (leaves. 46-49)
Text in English; Abstract: Turkish and English
Keywords: Waste management; Karaburun Peninsula; Izmir Peninsula; Sustainability; Environmental management